Application of SARAX code system on the calculation of complex unstructured geometry core - XIAO Bowen; ZHENG Youqi; WANG Yongping; QIAO Liang; TAO Yushan; LIU Xiaoyue (He jishu, 2023)
BackgroundWith the increase of complexity of reactor core design, the core modeling and calculation have brought challenges.PurposeThis study aims to implement the accurate modeling and calculation of unstructured geometry core.MethodsBased on discrete ordinate nodal method for arbitrary triangular-z geometry, the precise modeling and mesh generation of unstructured core were established by constructive solid geometry (CSG), and Block-Jacobi parallel algorithm was employed to reduce calculation time of reactor core. Finally, based on the developed SARAX program, core physics calculations for new complex geometries of a space reactor and a heat pipe reactor were performed for accuracy verification by using Block-Jacobi parallel algorithm combining with established precise model and mesh.ResultsThe verification results show that the effective multiplication factor and radial power distribution agree with that of multi-group Monte-Carlo calculation. The calculation deviation of eigenvalues is less than 3.00×10-3, and the relative deviation of radial power distribution is less than 1.5%.ConclusionsResults of this study show that SARAX code has the ability of modeling and higher accuracy in the calculation of unstructured geometry core.